ALK-positive large B-cell lymphomas: A clinicopathologic study - Chandramohan, Jagan; Ganapule, Gautami; Sigamani, Elanthenral; George, Biju; Korula, Anu; Manipadam, Marie (Indian journal of pathology & microbiology, 2022)
Background and Aim: Anaplastic lymphoma kinase (ALK)-positive large B-cell lymphomas (ALK+-LBCLs) are aggressive CD20-negative lymphomas, accounting for <1% of diffuse LBCLs. Being rare and with peculiar immunophenotypic characteristics, these can be easily misdiagnosed. We present 11 cases of ALK+-LBCLs diagnosed over a period of 11 years at a tertiary care hospital in South India to analyze the clinical, morphological, and immunophenotypic profile of these tumors. Subjects and Methods: ALK+-LBCL cases diagnosed from September 2009 to August 2020 were included. Clinical details were obtained from stored electronic records and summarized. Available hematoxylin and eosin (H and E) stained slides and immunohistochemistry slides were reviewed and observations tabulated. Results: Eleven patients (nine males and two females) were diagnosed with ALK+-LBCLs in the study period with seven presenting primarily with extranodal disease manifestations. Tumors in the lymph nodes showed diffuse architecture effacement and variable sinusoidal invasion. All tumors showed immunoblastic and plasmablastic-type large lymphoid cells with scattered anaplastic/multinucleate large cells, including rare Reed-Sternberg-like cells. Cytoplasmic granular ALK-1 staining, CD20 negativity, and immunohistochemical features of plasmablastic differentiation were noted in all. Of eight patients treated, only one achieved remission with multi-agent chemotherapy but relapsed after 6 months. Two patients died of disease and five others had progressive/persistent disease and were lost to follow-up. Conclusion: Although rare, these tumors should always be in the differential diagnoses of tumors with plasmablastic and immunoblastic morphology, especially in extranodal sites to avoid diagnostic delay/misdiagnosis.